Pengaruh perputaran kas dan perputaran piutang serta jumlah nasabah kredit terhadap return on asset pada lembaga perkreditan desa di kecamatan kubu - Jaya, I Kadek Susena Atma; Cipta, Wayan (Universitas Pendidikan Ganesha, 2021)
This study aims to examine the effect of cash turnover and accounts receivable turnover and the total of credit customers on return on assets. The design of this research is quantitative causal. The subject of this research was the LPD in Kubu District in 2019 with a population of 30 LPDs. The data were collected by document recording and analysed by multiple linear regression analysis. The results of this study indicate that (1) the level of cash turnover, accounts receivable turnover and the total of credit customers simultaneously effect to return on assets, (2) the rate of cash turnover has a positive and significant effect to return on assets, (3) accounts receivable turnover has a positive and significant effect to return on assets, (4) the total of credit customers has a positive and significant effect to return on assets.Â Keywords: cash turnover, credit customers, accounts receivable turnove, return on assets.Â